Simulation on characteristics of photo-hydrogen production and substrate degradation under various stacking types. (7th September 2015) - Guo, Cheng-Long; Pei, Hong-Shan; Cao, Hong-Xia; Guo, Fei-Qiang; Liu, Da-Meng; Li, Yi-Min
Abstract: A multiphase mixture model was developed for investigating the characteristics of photo-hydrogen production and substrate degradation under various stacking types. In this work, the entrapped-cell photobioreactor was packed with gel granules containing photosynthetic bacteria (PSB) and the effect of organic loading rate ( OLR ) on the performances of photo-hydrogen production and substrate degradation was studied. It was presented that the numerical simulation results were in good agreement with the reported experimental data, and the relative deviations between the reported experimental data and the numerical simulation results are within the range of −2.8 to +12.4% and −2.9 to +8.4% for the hydrogen production rate ( HPR ) and substrate degradation efficiency ( SDE ), respectively. Moreover, the effects of the OLR and the height of photobioreactor ( H ) under various stacking types were also explored. The results showed that the decrease of the OLR from 7.2 to 4.2 mmol/h and the increase of the H from 0.1 to 0.2 m led to the lower HPR, but were beneficial to enhance the SDE . In addition, more closely stacking type can improve the performances of photo-hydrogen production and substrate degradation owing to the increased mass transfer amount of substrate and products. Highlights: A multiphase mixture model is developed under various stacking types. Simulation results were in good agreement with the experimental data. Closely stacking type can enhance photo-hydrogen production performance.